2015
DOI: 10.1210/jc.2014-3969
|View full text |Cite|
|
Sign up to set email alerts
|

Human HtrA4 Expression Is Restricted to the Placenta, Is Significantly Up-Regulated in Early-Onset Preeclampsia, and High Levels of HtrA4 Cause Endothelial Dysfunction

Abstract: HtrA4 represents a novel placenta-specific serine protease that is altered specifically in early-onset PE with potential causal roles in endothelial dysfunction and disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 50 publications
0
68
0
Order By: Relevance
“…Thus, it is possible that HtrA1/3 may function antagonistically to HtrA4 during embryo implantation. During normal pregnancy the HtrA4 expression level changes and its aberrations have been correlated with preeclampsia [88,90]. HtrA4 may also, like HtrA1/3, modulate the ECM proteins e it has already been shown that it cleaves fibronectin in vitro [89].…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 99%
“…Thus, it is possible that HtrA1/3 may function antagonistically to HtrA4 during embryo implantation. During normal pregnancy the HtrA4 expression level changes and its aberrations have been correlated with preeclampsia [88,90]. HtrA4 may also, like HtrA1/3, modulate the ECM proteins e it has already been shown that it cleaves fibronectin in vitro [89].…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 99%
“…We have recently reported that high temperature requirement A4 (HtrA4) is a placenta-specific protease that is significantly increased in the circulation of early-onset PE [23]. HtrA4 belongs to a serine protease family that also includes HtrA1, HtrA2 and HtrA3.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, HTRA participates in the regulation of cell death, cell signalling and motility, apoptosis, and other processes [Singh et al, 2015]. Interestingly, in a fusion with Rv1196 protein, an M. tuberculosis HtrA (called Rv0125) has shown to enhance the protection conferred by BCG in M. tuberculosis -infected guinea pigs [Brandt et al, 2004].…”
Section: Resultsmentioning
confidence: 99%